“Universality plus difference"? Notes on cosmopolitanism and music (Revista Argentina de Musicología, 2024)
In recent decades, the concept of cosmopolitanism has acquired considerable relevance in different areas of knowledge, which is reflected in a profuse multidisciplinary bibliography. In the theoretical discussion, this notion is far from a consensus, partly due to the different ideological and disciplinary perspectives at play. The aim here is to explore some of these perspectives in order to reflect on a significant repertoire of situations in twentieth-century Latin American classical music, in which the tensions between belonging and exclusion are manifested, in relation both to local traditions and to international languages.
Keywords: cosmopolitanism; Latin American Art Music; identities